Environmental stress and emotional reactivity: an exploratory experience sampling method study - Wong, Corine Sau Man; Chan, Wai Chi; Lo, Kristen Wing Yan; Chen, Eric Yu Hai; Lam, Linda Chiu Wa (Frontiers in Psychiatry, 2024)
Background Previous studies have shown a relationship between environments and mental health. However, limited studies have investigated the impact of environment stress (ES) on emotional reactivity. Our study aimed to fill this gap by examining how daily ES affects momentary emotional reactivity using experience sampling method (ESM). Methods Participants were randomly recruited from a prospective cohort study in Hong Kong to participate in a 7-day ESM study. The participants received eight electronic signals daily assessing their ES, positive affect (PA) and negative affect (NA). Participants were categorized into depressed group or control group based on Revised Clinical Interview Schedule. Psychometric properties of the ESM assessment were evaluated. Multilevel linear regression analyzes were conducted to examine the association of ES with PA, NA and the group status of the participants (cases versus controls). Results A total of 15 participants with depression and 15 healthy controls were recruited, and 1307 momentary assessments were completed with a compliance rate of 77.8%. The depressed group demonstrated a significant increase in NA in response to ES, while the control group showed a decrease in PA. In addition, the depressed group reported a lower perception of control and interaction with their environment compared to the control group. Conclusion Using ESM, a valid, reliable, and easy-to-use self-reporting tool, our findings provided valuable insights on the potential mechanisms underlying emotional responses to stressful environments.